Tensión entre derechos y principios. Consideraciones a la interpretación judicial de la moral en la praxis del derecho (2014)
Dworking states that all legal propositions have a role in the complex network that composes the legal system and, also, they are able to have a determined meaning in that network; in such a manner, in the cases where judges face problems that include moral standards –such as torture, abortion or euthanasia- by virtue of the difficulty to determine the truth or falsity of the proposition, is neither possible to define if its legal or not, when establishing its practical importance. It is convenient to establish if moral criteria could indicate the thruth of legal norms (understood as legal propositions) and, in case they are thruth, in what events could they be . The purpose is to establish if judges consider these moral criteria into when deciding if a certain legal proposition is true.